The Effect of Compassionate Love on Peer Bullying in High School Students - Yıldırım GENE; Sefa BULUT (Yaşam Becerileri Psikoloji Dergisi, 2023)
The aim of this study is to examine the relationship between high school students' compassionate love levels and peer bullying behaviors. The sample of the research consists of a total of 560 high school students attending the 9th, 10th and 11th grades of Anatolian High School and Vocational and Technical Anatolian High School in Kağıthane district of Istanbul province in the 2020-2021 academic year. Personal Information Form, Compassionate Love Scale and Peer Bullying Scale Adolescent Form were used to collect data. In this research, the relational scanning model, one of the descriptive research types, was used. Pearson Product-Moment Correlation Coefficient was used to examine the relationship between Compassionate Love Scale Scores and Peer Bullying, Bully-Victim Subscale Scores and Total Scores, and Regression Analysis was used to test the effect of independent variables on the dependent variable. As a result of the research, it was determined that there was a weak, statistically significant negative relationship between high school students' compassionate love levels and being victims of peer bullying. The Regression Analysis of the Compassionate Love Scale scores with the peer bullying victim scale scores was found to be significant. Compassionate Love Scale scores explain 4% of the variance in peer bullying victim subscale scores.